Understanding linkages between common agricultural policy and High Nature Value (HNV) farmland provision: An empirical analysis in Tuscany region - Fabio Bartolini; Gianluca Brunori (Agricultural and Food Economics, 2014)
The connection between agriculture and environment is a central topic to the agricultural policy agenda and it has been the core of policy reforms. These linkages have been strengthened by the 2003 Common Agricultural Policy (CAP) Reform that has introduced a set of environmental rules as a condition to receive Single Farm Payments (SFP). Consequently, the provision of environmental goods is addressed by both CAP pillars I and II, respectively, with cross-compliance belonging to pillar I while the second axis Rural Development Program (RDP) measures belong to the pillar II. The aim of this paper is to analyse the provision of environmental goods provided by agricultural activities and the impact the Common Agricultural Policy has on such provision. This aim is pursued firstly by quantifying an environmental quality indicator based on the concept of High Nature Value (HNV) farmland and, secondly by testing Exploratory Spatial Data Analysis (ESDA) techniques and spatial econometric models as means to identify provision determinants that improve causality in spatially non-stationary data. The analysis highlights the relevance of spatial models in improving the quality of the estimation, while model results show that rural development program measures and income support payments have opposite effects. Results confirm the relevance of productive factor use and entrepreneurship in explaining differences on environmental quality provision.
Keywords: 330; Common agricultural policy; High nature value; Policy impacts; Spatial econometrics; Exploratory Spatial Data Analysis (ESDA); Agri-environmental schemes (AES)